2021
DOI: 10.1177/11206721211057695
|View full text |Cite
|
Sign up to set email alerts
|

Macular and peripapillary microvasculature after dexamethasone injection in diabetic macular edema

Abstract: Purpose To evaluate the microvascular changes in the macular and peripapillary area after intravitreal dexamethasone implant in diabetic macular edema (DME) Material and Methods We included 31 eyes of 31 patients treated with a single dose dexamethasone implant for DME. All subjects underwent swept-source optical coherence tomography (OCT) and OCT angiography imaging before (T0), and one month (T1), two months (T2), and four months (T4) after dexamethasone injection. The foveal avascular zone (FAZ) area of sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
2
1
Order By: Relevance
“…Similar to some previous studies, we found in the present study that there was no significant change in the vessel density of the SCP and DCP, with the exception of two quadrants of the superior and inferior SCP. In contrast, the present study did show that there was significant enlargement of the FAZ area after the administration of TA (before: 0.29 ± 0.10 mm 2 , after: 0.32 ± 0.13 mm 2 p < 0.041), which is not consistent with the previous report on the intravitreal dexamethasone implant [23][24][25]. To the best of our knowledge, at the present time, there have been no data reported on OCTA parameters that include information on microaneurysms after the intravitreal injection of TA.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similar to some previous studies, we found in the present study that there was no significant change in the vessel density of the SCP and DCP, with the exception of two quadrants of the superior and inferior SCP. In contrast, the present study did show that there was significant enlargement of the FAZ area after the administration of TA (before: 0.29 ± 0.10 mm 2 , after: 0.32 ± 0.13 mm 2 p < 0.041), which is not consistent with the previous report on the intravitreal dexamethasone implant [23][24][25]. To the best of our knowledge, at the present time, there have been no data reported on OCTA parameters that include information on microaneurysms after the intravitreal injection of TA.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings were not confounded in the patients on steroids. However, there are other studies that found that there were no significant changes in the vessel density (SCP and DCP) [22][23][24] and that there was a decrease in the FAZ area after an intravitreal dexamethasone implant [23,24]. In contrast, Carnota-Méndez et al reported finding that there was a reduction in the vessel density and vascular perfusion in the absence of any changes in the FAZ area after the administration of dexamethasone [25].…”
Section: Discussionmentioning
confidence: 96%
“…Our results showed that DEX-I seems to have no side effects on RNFL thickness, IOP and peripapillary VD in a 1-month period. Similarly, Ozcalıskan et al 31 found macular reperfusion after DEX-I with no significant impact on peripapillary capillaries in DME patients. The long-term DEX-I effects on the RNFL are not well known.…”
Section: Discussionmentioning
confidence: 86%